A PRELIMINARY STUDY ON THE READINESS OF BLENDED LEARNING AMONG LECTURERS AT UNIVERSITI UTARA MALAYSIA (Practitioner Research, 2021)
The modern way of teaching and learning emphasizes the technology to be embedded in the education system. Thus, higher learning institutions (HLIs) are gradually switching their class delivering method from classroom-based teaching (CBT) to the so-called blended learning approach (BLA). The BLA integrates traditional CBT with the online teaching class. Thus, this study aims to investigate the readiness level towards BLA among lecturers in HLIs. UUM lecturers were chosen as a study population, and the sample of 350 lecturers was determined using a proportionate random sampling method. The survey method was used to gather the data and by utilizing the descriptive statistic, our results suggest that lecturers in HLIs have a high level of readiness towards the BLA. Even though there is some limitation, they are keen to participate in the BLA.  The findings of this study will help HLIs to understand the readiness level of lecturers towards BLA, explicate how face-to-face and online class could be integrated, besides accommodates the loopholes in the system.